Green open space in large scale housing estates: a place for challenge - Treija, Sandra; Bratuškins, Ugis; Bondars, Edgars (Journal of Architecture and Urbanism, 2013)
The renewal of urban areas by developing green open spaces increases the overall quality of life and helps to reduce social exclusion. Urban green open space can help to constitute a framework where urban society and culture can develop, and to increase identity and a sense of community. It can be used to provide a ground for education and raise an awareness of the way ecosystems function and how urban functions can be integrated into the natural system. Despite the known socio-economic benefits resulting from it, considerations regarding sustainable land use planning often occupy a secondary role when designing city quarters. There exist many pressures – essentially market-related and driven by short-term thinking – for unsustainable development. Housing ownership reform, carrying out denationalization and privatization, along with a core capital for many inhabitants has also created a range of problems – one of them: as a result of denationalisation of land properties, when the land in large-scale residential districts was returned to the previous owners and then provided as the minimum required land to the privatised buildings, the original spatial composition of districts was completely destroyed, creating a legal basis for new construction in large-scale residential districts.